Ecuador´s, Chile´s and Mexico´s journalists’ satisfaction in relation to university education and its implications in professional practice - Gutiérrez Atala, Fernando (2019)
In the context of an information and knowledge society in which technological development is moving ahead at a staggering speed, probing the sense of sufficiency in the graduates active in the field of work is presented as an imperative need for the profession´s improvement and its teaching. The objective of this study is to determine the journalistic perception about university education and the satisfaction level of journalists with their university education, including aspects of technical, theoretical and practical management. To meet this aim, forty semi-structured interviews have been conducted with active Chilean, Ecuadorian and Mexican journalists, from the four media (press, television, radio and internet). The findings show that although the importance given to academic training in professional development varies according to the country, Chilean, Ecuadorian and Mexican journalists perceive a series of shortcomings in their educational systems, which needs a reframing of Communication and Journalism careers.